Nano- and micro-based inhaled drug delivery systems for targeting alveolar macrophages. (June 2015) - Lee, Wing-Hin; Loo, Ching-Yee; Traini, Daniela; Young, Paul M
<x xml:space="preserve">Abstract</x> Introduction: Macrophages are the most versatile cells in the hematopoietic system and are strategically distributed in tissues to fight pathogens or other foreign particles. In the lung, however, for intracellular infections such as tuberculosis, pneumonia and aspergillosis, bacteria and fungi utilize the alveolar macrophage as a breeding ground. This has become a challenge for the treatment of these infections, as most drugs do not effectively reach the macrophages at therapeutic levels. Alveolar macrophages also play an important role to initiative adaptive immunity toward combating inflammation and cancer in the lung. Areas covered: This review focuses on the development of micro- and nanotechnology-based drug delivery systems to target alveolar macrophages in association with intracellular infections, cancer and lung inflammation. Aspects of nanoparticle and micron-sized particle engineering through exploitation of particles' physicochemical characteristics such as particle size, surface charge and geometry of particles are discussed. In addition, the application of nanocarriers such as liposomes, polymeric nanoparticles and dendrimers are covered with respect to macrophage targeting. Expert opinion: Drug delivery targeted to alveolar macrophages in the lung is becoming a reality thanks to micro- and nanotechnology breakthrough. The literature review shows that regulation of physicochemical parameters of particles could be a recipe to enhance macrophage targeting and uptake. However, there is still a need to identify more target-specific receptors in order to facilitate drug targeting. Besides that, the toxicity of nanocarriers arising from prolonged residence in the lung should be taken into consideration during formulation.